2012
DOI: 10.1002/ejoc.201200643
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of Carbazole‐Type D‐π‐A Fluorescent Dyes Possessing Solid‐State Red Fluorescence Properties

Abstract: Carbazole‐type donor‐π‐acceptor (D‐π‐A) fluorescent dyes (SO1 and SO2), each containing a diphenylamino system as an electron‐donating group and a nitro moiety as an electron‐accepting group, have been designed and synthesized, and their photophysical properties in solution and in the solid state have been investigated. The absorption and fluorescence properties of SO1 and SO2 in solution are similar, and both dyes exhibited moderate fluorescence quantum yields. In the solid state, however, the dye SO2, with a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 70 publications
0
7
0
Order By: Relevance
“…e l abs, ex, or -solid max (heating) À l abs, ex, or -solid max (grinding). with the case of D-p-A-type uorescent dyes, [11][12][13][14][15] the MFC of the (D-p-) 2 A-type azine-based uorescent dyes was not just a matter of events originating from a reversible change between crystalline and amorphous states by grinding and heating, because OUY-2 as well as OTK-2 exhibited non-obvious MFC. More interestingly, the densities of the solids measured by the Archimedian method were found to increase by grinding from 1.40, 1.26, 1.25, and 1.13 g cm À3 to 1.45, 1.37, 1.39, and 1.31 g cm À3 for OTK-2, OUY-2, OUK-2, and OUJ-2, respectively, indicating that the dye molecules in the amorphous state aer grinding were more densely packed.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…e l abs, ex, or -solid max (heating) À l abs, ex, or -solid max (grinding). with the case of D-p-A-type uorescent dyes, [11][12][13][14][15] the MFC of the (D-p-) 2 A-type azine-based uorescent dyes was not just a matter of events originating from a reversible change between crystalline and amorphous states by grinding and heating, because OUY-2 as well as OTK-2 exhibited non-obvious MFC. More interestingly, the densities of the solids measured by the Archimedian method were found to increase by grinding from 1.40, 1.26, 1.25, and 1.13 g cm À3 to 1.45, 1.37, 1.39, and 1.31 g cm À3 for OTK-2, OUY-2, OUK-2, and OUJ-2, respectively, indicating that the dye molecules in the amorphous state aer grinding were more densely packed.…”
Section: Resultsmentioning
confidence: 99%
“…8 debye) show weak MFC due to the strong dipole–dipole interactions between the dye molecules, changes in which may be inhibited in the crystal-to-amorphous phase transition. 14 Moreover, it was suggested that negligible MFC observed in D–π–A-type fluorescent dyes possessing small dipole moments ( μ g = ca. 1–2 debye) is ascribable to small changes in the dipole–dipole interactions between the crystalline and amorphous states.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…13 The absorption band at around 320 nm is attributed to the local p / p* transition. 20 The uorescence maximum appears at 535 nm for YHO-2 and 536 nm for YHO-3, respectively, which occurs from the BODIPY locally excited (LE) state. The uorescence quantum yields (F) of YHO-2 and YHO-3 are 0.62 and 0.70, respectively.…”
Section: Spectroscopic Properties Of Yho-2 and Yho-3 In Solutionmentioning
confidence: 99%
“…On the other hand, recent works highlighted the interest of simple and small molecular weight D-π-A push-pull dipolar fluorophores, in which an electron donating group D is connected to an electron-withdrawing group A via a π-conjugated bridge, for the design of efficient solid-state emitters. [22][23][24][25][26][27] , [28][29][30][31] , [32][33][34][35][36][37][38][39] , [40] , [41] The permanent dipole moment associated with the D-π-A structure gives rise to strong dipole-dipole interactions that can induce specific organization and orientation of molecules in the solid-state and favors the formation of emissive aggregates. Moreover, since the fluorescence of such dipolar fluorophores is usually characterized by a large Stokes shift, red and even far-red emission wavelengths over 700 nm are accessible, providing appropriate combinations of electron-donor and acceptor groups.…”
Section: Introductionmentioning
confidence: 99%